2019
DOI: 10.1155/2019/7483537
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Beta Gene Polymorphism rs16944 May Associate with Increased Susceptibility to Extremity Chronic Osteomyelitis in Chinese Han Population

Abstract: Background. Previous studies had indicated that interleukin-1 beta (IL-1β) gene single nucleotide polymorphisms (SNPs) associate with different inflammatory diseases. However, potential links between these polymorphisms and susceptibility to extremity chronic osteomyelitis (COM) remain unclear. This study aimed to investigate relationships between IL-1β gene polymorphisms (rs16944, rs1143627, rs1143634, and rs2853550) and risks of developing extremity COM in Chinese Han population. Methods. Altogether 233 extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…First, we found that IL-1β gene rs16944 correlates with an increased risk of PTOM development, with AG and GG genotypes as risk factors. The present outcomes share both similarities and differences with previous studies [8,20,21]. We agree with the previous conclusions that rs16944 is a risk factor of OM, regardless of OM etiology (trauma, hematogenous spread) and population (Chinese, Saudi, and Brazilian).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, we found that IL-1β gene rs16944 correlates with an increased risk of PTOM development, with AG and GG genotypes as risk factors. The present outcomes share both similarities and differences with previous studies [8,20,21]. We agree with the previous conclusions that rs16944 is a risk factor of OM, regardless of OM etiology (trauma, hematogenous spread) and population (Chinese, Saudi, and Brazilian).…”
Section: Discussionsupporting
confidence: 92%
“…Second, we found that IL-1β gene rs1143627 also associates with an elevated susceptibility to PTOM, with TT genotype as a risk factor. While in the previous study [20], we failed to obtain any significant links between the two, which is probably because of the inclusion of the non-PTOM patients. Although no statistical differences were identified regarding the genotype distribution, mutant allele frequency, or the heterozygous model between the two groups, their P values were close to 0.05, implying that the mutant allele T may be a risk factor and population with CT genotype may be in a higher risk to develop PTOM.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A burgeoning body of evidence underscores the potential role of genetic variants, specifically single nucleotide polymorphisms (SNPs), in shaping the susceptibility to OM. Noteworthy instances include genetic variants at loci such as Bax-Gene G (-248) (rs4645878), IFN-γ (rs2430561), IL-1β (rs1143634), and TLR-2 (rs3804099), which have demonstrated associations with heightened vulnerability to hematogenous or traumatic OM across diverse ethnic cohorts [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Furthermore, IL1B polymorphism rs16944 is associated with multiple inflammatory diseases such as chronic periodontitis, coronary artery lesions and chronic osteomyelitis. [ 8 10 ] Therefore, it is conceivable that IL1B polymorphism rs1143623 and rs16944 potentially have the closely related to inflammatory diseases, such as GDM.…”
Section: Introductionmentioning
confidence: 99%